2023
DOI: 10.1097/gox.0000000000004928
|View full text |Cite
|
Sign up to set email alerts
|

A Consensus Approach for Targeted Muscle Reinnervation in Amputees

Abstract: Amputations have been performed with few modifications since the dawn of surgery. Blood vessels are ligated, bones are shortened, and nerves are cut. In a percentage of people, this can result in severe neuropathic, residual limb, and phantom limb pain. Targeted muscle reinnervation is a surgical procedure initially conceived to optimize function for myoelectric prostheses in amputees. Recently, it has been adopted more widely by surgeons for the prevention and treatment of neuropathic pain. Perhaps as a funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Identification of nerves and potential nerve targets form TMR is performed based on published consensus guidelines. 9…”
Section: Operative Techniquementioning
confidence: 99%
“…Identification of nerves and potential nerve targets form TMR is performed based on published consensus guidelines. 9…”
Section: Operative Techniquementioning
confidence: 99%
“…3 There are three critical steps in TMR surgery: (1) recognizing the donor major sensory or mixed motor/sensory nerve, (2) identifying the recipient motor nerve branches to the target muscle, and (3) securing a functional nerve coaptation. 4…”
Section: Introductionmentioning
confidence: 99%
“…3 There are three critical steps in TMR surgery: (1) recognizing the donor major sensory or mixed motor/sensory nerve, (2) identifying the recipient motor nerve branches to the target muscle, and (3) securing a functional nerve coaptation. 4 During our experience with handheld peripheral nerve stimulators, the authors have developed several strategies that improve speed and accuracy during peripheral nerve surgery and may assist in a wide range of procedures performed by peripheral nerve surgeons. In this article, three useful tips and tricks are demonstrated in handheld intraoperative nerve stimulation to perform TMR and peripheral nerve surgery efficiently and successfully.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] As a relatively novel modality, TMR has gained popularity for the treatment of these sequela and its utilization as a prophylactic modality is being more widely adopted across the United States. 5 However, it has been identified that access to this technique at time of amputation (primary TMR) is not always available for many geographical locations. 6 Differences in location and socioeconomic factors, expressed as Area Deprivation Index (ADI) score, 7 have been linked to worse pain coping and social support.…”
Section: Introductionmentioning
confidence: 99%